2018
DOI: 10.1111/jnc.14535
|View full text |Cite
|
Sign up to set email alerts
|

Neuritin promotes neurite and spine growth in rat cerebellar granule cells via L‐type calcium channel‐mediated calcium influx

Abstract: Neuritin is a neurotrophic factor that is activated by neural activity and neurotrophins. Its major function is to promote neurite growth and branching; however, the underlying mechanisms are not fully understood. To address this issue, this study investigated the effects of neuritin on neurite and spine growth and intracellular Ca2+ concentration in rat cerebellar granule neurons (CGNs). Incubation of CGNs for 24 h with neuritin increased neurite length and spine density; this effect was mimicked by insulin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Neuritin activity can also be mediated through nuclear factor of activated T-cells cytoplasmic 4 (NFATc4) and calcineurin (CaN). Neuritin induces neurite morphological changes through calcium signaling by upregulating L-type voltage gated calcium channels (Zhao et al, 2018 ). Additionally, the trophic factor fibroblast growth factor (FGF) appears to mediate the activity-dependent neurite morphological effects of neuritin.…”
Section: Mechanisms Of Neuronal Activity-associated Plasticitymentioning
confidence: 99%
“…Neuritin activity can also be mediated through nuclear factor of activated T-cells cytoplasmic 4 (NFATc4) and calcineurin (CaN). Neuritin induces neurite morphological changes through calcium signaling by upregulating L-type voltage gated calcium channels (Zhao et al, 2018 ). Additionally, the trophic factor fibroblast growth factor (FGF) appears to mediate the activity-dependent neurite morphological effects of neuritin.…”
Section: Mechanisms Of Neuronal Activity-associated Plasticitymentioning
confidence: 99%
“…Knocking down ALKBH1 resulted in impaired sensory axon regeneration in vitro and in vivo, which could be rescued by simultaneously knocking down N6AMT1. Moreover, we observed that deleting ALKBH1 resulted in down regulation of several neurodevelopmental related genes, such as Id1 and neuritin, proteins known to regulate axon growth and regeneration (Gao et al, 2016;Huang et al, 2020;Huang et al, 2019;Lasorella et al, 2005;Sharma et al, 2015;Zhao et al, 2018). Collectively, our study not only discovered a new physiological function of ALKBH1 in neurons, but also illustrated a novel epigenetic regulatory mechanism underlying mammalian axon regeneration.…”
Section: Introductionmentioning
confidence: 55%
“…Interestingly, several of these 5 genes have been shown to regulate axon growth or regeneration. For instance, Nrn1 that encodes the protein neuritin is well known to promote axon growth and optic nerve regeneration (Gao et al, 2016;Huang et al, 2020;Sharma et al, 2015;Zhao et al, 2018). In addition, the transcription factor Id1 and its homolog Id2 have been shown to be involved in regulation of axon growth and regeneration (Huang et al, 2019;Lasorella et al, 2005).…”
Section: Down Regulation Of Alkbh1 Resulted In Changed Expression Of Neurodevelopmental Related Genesmentioning
confidence: 99%
“…Given the greater changes in NRN1 levels, compared to GAP43, in FUS mutant MNs, we decided to prioritize this candidate for further analysis. Upon activation by neural activity and neurotrophins, NRN1 plays a positive role in promoting neurite outgrowth and arborization [42][43][44][45][46].…”
Section: Aberrant Axonal Phenotypes Of Mutant Motoneurons Are Due To mentioning
confidence: 99%